Heat transfer and sensitivity analysis in a double pipe heat exchanger filled with porous medium - Shirvan, Kamel Milani; Mirzakhanlari, Soroush; Kalogirou, Soteris A.; Öztop, Hakan Fehmi; Mamourian, Mojtaba (Elsevier France-Editions Scientifiques Medicales Elsevier, 2017)
In this paper, 2-D numerical investigation and sensitivity analysis are performed on heat transfer rate and heat exchanger effectiveness of a double pipe heat exchanger filled with porous medium. The Darcy -Brinkman-Forchheimer model is applied to model the flow field in the porous zone. The sensitivity analysis is performed utilizing the Response Surface Methodology. The studied parameters are: Reynolds number (50 <= Re <= 250), Darcy number (10(-5) <= Da <= 10(-3)), temperature difference between hot and cold fluids (30 <= Delta T <= 70) and the porous substrate thickness (1/3 <= delta <= 1). The obtained results showed that enhancement of the Nusselt number due to the increase in Reynolds and Darcy numbers is in the vicinity of the 77.84% for the case with delta = 2/3 and Da =10(-5) to 10(-3), and 203.25% for the case with delta =1 and Re = 50 to 250. Furthermore, increasing porous substrate thickness reduces the mean Nusselt number until delta = 2/3 and then increases it. In addition, it is found that the heat exchanger effectiveness increases with the Re number and reduces with enhancement of the Da number. The sensitivity analysis showed that the sensitivity of the mean Nusselt number to the Re and Da numbers and the porous substrate thickness is positive, while the sensitivity of the heat exchanger effectiveness to the Re number is positive but to the Da number is negative. (C) 2017 Elsevier Masson SAS. All rights reserved.
Keywords: Response surface methodology; Sensitivity analysis; Heat exchanger effectiveness double pipe; heat exchanger; Heat transfer; Porous medium